Aktivitas Antibakteri Actinomycetes yang Diisolasi dari Rizosfer Tanaman Solanaceae - Umi Fatmawati; Slamet Santosa; Yudi Rinanto; Riezky Maya Probosari (Fakultas Farmasi Universitas Setia Budi, 2014)
Actinomycetes is one type of microorganism that has been widely used for the production of antibiotics as well as a biological control for pests and diseases in plants. In general, many Actinomycetes distributed in soil, water, tissues endophyte, and other natural environments. The study aimed to determine the distribution and diversity of Actinomycetes found in the root zone at Solanaceae plants and to know the isolates of Actinomycetes isolated from the root zone of plants Soalaneceae could inhibiting the growth of bacteria. Actinomycetes isolated from seven soil samples of Solanaceae plants rhizosphere in Selo Boyolali, Colomadu Karanganyar, Gondangrejo Karanganyar, and Wonogiri Jatipurno. The isolates of Actinomycetes tested the antibacterial activity by well diffusion method on media Glycerol-Yeast Extract against four species of pathogenic bacteria Ralstonia solanacearum, Staphylococcus aureus, Bacillus subtilis and Escherichia coli. Results showed that there were 54 isolates of Actinomycetes isolated from the soil samples of Solanaceae plants rhizosphere. Isolates could inhibit the growth of R. solanacearum (29%), S. aureus (24%), B. subtillis (14%), and E. coli (7%). Isolates had the ability to degrade carbohydrate and protein.